The Relationship Between Parental Knowledge and The Problem of Nutritional Deficiency in Early Children in Jorong Pasia Laweh Agam Regency - Riri Kesuma Deva; Ismaniar Ismaniar (Universitas Negeri Padang, 2023)
The aim of this research is to determine the description and relationship between parental knowledge and malnutrition in children in Jorong Pasia Laweh. This research uses a correlational quantitative approach. The population of this study was 59 parents who had children with malnutrition in Jorong Pasia Laweh. The sampling technique in this research was carried out using the Cluster Random Sampling method, so the total sample that the researchers took was 75% of the total population of 59 people, namely 44 people. The data collection technique in this research is a questionnaire. The data analysis method in this research is the product moment correlation method. The results of this research are: 1.) The level of knowledge of parents about nutrition in Jorong Pasia Laweh is classified as less effective, because the answers of respondents who chose almost half of the parents who answered did not agree with the level of knowledge of parents about nutrition in Jorong Pasia Laweh. 2.) The nutritional adequacy condition of children in Jorong Pasia Laweh is classified as less effective, because almost half of the parents who answered did not agree with the nutritional adequacy condition of children in Jorong Pasia Laweh and 3.) There is a significant relationship between parental knowledge and malnutrition in children in Jorong Pasia Laweh. This is proven by r count > r table so Ho is rejected and conversely Ha is accepted. So the conclusion is that there is a significant relationship between parental knowledge and malnutrition in children in Jorong Pasia Laweh.Keywords: Parental Knowledge, Malnutrition.